Analysis of deep levels in a phenylenevinylene polymer by transient capacitance methods - Gomes, Henrique L. (2015)
Transient capacitance methods were applied to the depletion region of an abrupt asymmetric n(+) -p junction of silicon and unintentionally doped poly[2-methoxy, 5 ethyl (2' hexyloxy) paraphenylenevinylene] (MEH-PPV). Studies in the temperature range 100-300 K show the presence of a majority-carrier trap at 1.0 eV and two minority traps at 0.7 and 1.3 eV, respectively. There is an indication for more levels for which the activation energy could not be determined. Furthermore, admittance data reveal a bulk activation energy for conduction of 0.12 eV, suggesting the presence of an additional shallow acceptor state. (C) 1999 American Institute of Physics. [S0003-6951(99)02308-6].